The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.20517/mrr.2022.20
|View full text |Cite
|
Sign up to set email alerts
|

The human microbiome project at ten years - some critical comments and reflections on “our third genome”, the human virome

Abstract: The Human Microbiome Project (HMP) has raised great expectations claiming the far-reaching influence of the microbiome on human health and disease ranging from obesity and malnutrition to effects going well beyond the gut. So far, with the notable exception of fecal microbiota transplantation in Clostridioides difficile infection, practical application of microbiome intervention has only achieved modest clinical effects. It is argued here that we need criteria for the link between microbiome and disease modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Studies have indicated that alterations in the microbiota composition, known as dysbiosis, may influence the development, progression, and prognosis of Pancreatic cancer. The Human Microbiome Project has shed light on the impact of microbial communities on human health and disease, including cancer [103]. Advanced biological technologies such as high-throughput sequencing, transcriptomics, and metabolomics have enabled researchers to gain a deeper understanding of the role of the microbiome in pancreatic cancer [104,105].…”
Section: Pancreatic Cancer and Microbiome Interactionmentioning
confidence: 99%
“…Studies have indicated that alterations in the microbiota composition, known as dysbiosis, may influence the development, progression, and prognosis of Pancreatic cancer. The Human Microbiome Project has shed light on the impact of microbial communities on human health and disease, including cancer [103]. Advanced biological technologies such as high-throughput sequencing, transcriptomics, and metabolomics have enabled researchers to gain a deeper understanding of the role of the microbiome in pancreatic cancer [104,105].…”
Section: Pancreatic Cancer and Microbiome Interactionmentioning
confidence: 99%
“…Most body sites typically contain a multitude of microbes resulting in diverse ecosystems. In contrast, sites in the human body dominated by one or a few species -dysbiosis -are often an indicator of disease [5][6][7].…”
Section: Introductionmentioning
confidence: 99%